Testing job wellbeing indicators among community behavioral health workers: Community-based participatory research - Sadaaki Fukui; Wei Wu; Jennifer Garabrant; Michelle P. Salyers; Nathaniel Dell; Emily Bass; Jaime Greenfield; Gary Morse (PLoS ONE, 2025)
Many community behavioral health organizations (CBHOs) continue to struggle with their employees’ reduced job wellbeing and job disengagement (i.e., turnover intentions, actual turnover). Understanding employees’ job wellbeing priorities in their organizational contexts is essential to address the challenges, especially for workers in diverse work settings such as CBHOs. We used community-based participatory research (CBPR) strategies to develop and test job wellbeing indicators. The current study implemented 11 indicators with 168 people employed at a CBHO through initial and 6-month follow-up surveys. Positive endorsement of job wellbeing indicators differed based on employees’ demographic (e.g., race, education, marital status) and job (e.g., exempt status, clinical positions) characteristics. Several indicators declined from the initial to the follow-up surveys (e.g., communication, job fairness, decision-making involvement, expectation alignment, supervisory support, career development opportunities). The change rates also varied by employee characteristics (e.g., work years, race, exempt status, full-time). The current study illustrates the utility of CBPR strategies to implement job wellbeing indicators based on employees’ priorities and diverse job wellbeing experiences among employee subpopulations. Further, the developed indicators revealed job wellbeing heterogeneity by employee subpopulations within an organization that is often overlooked. Efforts to understand varying job wellbeing characteristics among diverse employees may eventually help develop organization-tailored interventions to improve job wellbeing and reduce turnover.